Effects of Subacute Treatment of Thiourea on Antioxidant and Immunopotential Marker Enzymes and Lipid Peroxidation of Rats: A Drinking Water Study - Celik, Ismail; Suzek, Huseyin; Tuluce, Yasin (Asian Journal of Chemistry, 2016)
The effect of subacute 25 days treatment of thiourea, an inhibitor of diene conjugate formation as hydroxyl radical scavengers were tested as terminators of lipid peroxidation (malondialdehyde = MDA), antioxidant [reduced glutathione (GSH), glutathione reductase (GR), glutathione peroxidase (GPx), gIutathione-S-transferase (GST), superoxide dismutase (SOD) and catalase (CAT] and immunopotential [adenosine deaminase (ADA) and myelo-peroxidase (MPO) defense systems marker enzymes in the liver tissue of rats under laboratory conditions. 250 ppm of thiourea was administered orally to 8 rats ad libitum during the tests for 25 days consecutively. Malondialdehyde content, antioxidant and immunopotential marker enzyme of liver were determined after treatment According to results, while the treatment of thiourea caused significant decrease in MDA content, GSH level, GR activity and immunopotentical enzyme activities decreased in comparison to control rats. CAT, GPx, SOD and GST activities did not change significantly. These results suggest that thiourea may not only reduce oxidative damage by induced oxygen reactive radicals in animals, but affect immunopotential enzymes too.